(3x-1)(x+2)=-1

Simple and best practice solution for (3x-1)(x+2)=-1 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for (3x-1)(x+2)=-1 equation:


Simplifying
(3x + -1)(x + 2) = -1

Reorder the terms:
(-1 + 3x)(x + 2) = -1

Reorder the terms:
(-1 + 3x)(2 + x) = -1

Multiply (-1 + 3x) * (2 + x)
(-1(2 + x) + 3x * (2 + x)) = -1
((2 * -1 + x * -1) + 3x * (2 + x)) = -1
((-2 + -1x) + 3x * (2 + x)) = -1
(-2 + -1x + (2 * 3x + x * 3x)) = -1
(-2 + -1x + (6x + 3x2)) = -1

Combine like terms: -1x + 6x = 5x
(-2 + 5x + 3x2) = -1

Solving
-2 + 5x + 3x2 = -1

Solving for variable 'x'.

Reorder the terms:
-2 + 1 + 5x + 3x2 = -1 + 1

Combine like terms: -2 + 1 = -1
-1 + 5x + 3x2 = -1 + 1

Combine like terms: -1 + 1 = 0
-1 + 5x + 3x2 = 0

Begin completing the square.  Divide all terms by
3 the coefficient of the squared term: 

Divide each side by '3'.
-0.3333333333 + 1.666666667x + x2 = 0

Move the constant term to the right:

Add '0.3333333333' to each side of the equation.
-0.3333333333 + 1.666666667x + 0.3333333333 + x2 = 0 + 0.3333333333

Reorder the terms:
-0.3333333333 + 0.3333333333 + 1.666666667x + x2 = 0 + 0.3333333333

Combine like terms: -0.3333333333 + 0.3333333333 = 0.0000000000
0.0000000000 + 1.666666667x + x2 = 0 + 0.3333333333
1.666666667x + x2 = 0 + 0.3333333333

Combine like terms: 0 + 0.3333333333 = 0.3333333333
1.666666667x + x2 = 0.3333333333

The x term is 1.666666667x.  Take half its coefficient (0.8333333335).
Square it (0.6944444447) and add it to both sides.

Add '0.6944444447' to each side of the equation.
1.666666667x + 0.6944444447 + x2 = 0.3333333333 + 0.6944444447

Reorder the terms:
0.6944444447 + 1.666666667x + x2 = 0.3333333333 + 0.6944444447

Combine like terms: 0.3333333333 + 0.6944444447 = 1.027777778
0.6944444447 + 1.666666667x + x2 = 1.027777778

Factor a perfect square on the left side:
(x + 0.8333333335)(x + 0.8333333335) = 1.027777778

Calculate the square root of the right side: 1.013793755

Break this problem into two subproblems by setting 
(x + 0.8333333335) equal to 1.013793755 and -1.013793755.

Subproblem 1

x + 0.8333333335 = 1.013793755 Simplifying x + 0.8333333335 = 1.013793755 Reorder the terms: 0.8333333335 + x = 1.013793755 Solving 0.8333333335 + x = 1.013793755 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-0.8333333335' to each side of the equation. 0.8333333335 + -0.8333333335 + x = 1.013793755 + -0.8333333335 Combine like terms: 0.8333333335 + -0.8333333335 = 0.0000000000 0.0000000000 + x = 1.013793755 + -0.8333333335 x = 1.013793755 + -0.8333333335 Combine like terms: 1.013793755 + -0.8333333335 = 0.1804604215 x = 0.1804604215 Simplifying x = 0.1804604215

Subproblem 2

x + 0.8333333335 = -1.013793755 Simplifying x + 0.8333333335 = -1.013793755 Reorder the terms: 0.8333333335 + x = -1.013793755 Solving 0.8333333335 + x = -1.013793755 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-0.8333333335' to each side of the equation. 0.8333333335 + -0.8333333335 + x = -1.013793755 + -0.8333333335 Combine like terms: 0.8333333335 + -0.8333333335 = 0.0000000000 0.0000000000 + x = -1.013793755 + -0.8333333335 x = -1.013793755 + -0.8333333335 Combine like terms: -1.013793755 + -0.8333333335 = -1.8471270885 x = -1.8471270885 Simplifying x = -1.8471270885

Solution

The solution to the problem is based on the solutions from the subproblems. x = {0.1804604215, -1.8471270885}

See similar equations:

| -x-3(-5x-8)=136 | | (12^5)/(9^2)*(4^4) | | 12^5/9^2*4^4 | | 0.3x-2(0.1x+0.4)= | | (3a-9)/(3a-6)*(a/a^2-9) | | {(3a-9)/(3a-6)}*(a/a^2-9) | | f(x)=-3.25(-4.2) | | 18=2v+4 | | 6+2(5x-1)=84 | | 18-12a= | | 108=-6(3+3x) | | 5h-3h+9h= | | 42n-12=0 | | Log(7)25=2log(7) | | 3a-9/3a-6*a/a^2-9 | | 7(4+h)=13h | | sin(2x-60)=-cos(3x) | | 121=-11b | | 5p-7=2p | | 90-x=0.8(x) | | 1/2d-12 | | 83=-3(6b+3)+2 | | x^2+y^2+8y=9 | | 40-10x=40+2x | | 11x+12=265 | | 2m-3n=1 | | 33=-5-2x | | (2x-5)=(45) | | 2x-5+45+80+105=360 | | 2/9x1/8= | | (d+2)*(d+2)=8 | | 8x+28-4x=20 |

Equations solver categories